Stakeholder Views of Real Estate Registration in Egypt and the Reform of 2022 - AlSisi, Karim (AUC Knowledge Fountain, 2026)
Real estate registration in Egypt has historically remained low despite the enactment of a deeds registration law in the 1940s and a title registration law in the 1960s. The 2022 reform (Law No. 9 of 2022) warranted an assessment of its effectiveness through a Public Policy and Administration lens. This thesis has two main objectives: first, to examine stakeholders’ views of the reform; and second, to explore stakeholder perspectives on formal registration and the factors driving registration avoidance by employing a qualitative design, using in-depth interviews with four stakeholder groups encompassing both system users and service providers. The findings revealed multiple themes covering the two research objectives describing – from the stakeholders’ perspectives – pre-reform barriers to registration such as absence of land registration, an overview of the reform and key amendments such as the introduction of the Verification of Occupation, benefits and drawbacks of the reform such as streamlining procedural steps, barriers faced during reform implementation such as poor staff training, priorities for future reform such as accelerating cadastral survey reports issuance, the benefits of formal registration such as swift resolution of ownership disputes, and factors leading to registration avoidance such as extra-governmental fees imposed by related entities. The Government of Egypt appears to have engaged stakeholders to identify and address many systemic barriers that have long plagued the system. Many obstacles that precluded real estate owners from registering, and impediments that were only surmountable at extra cost, time, and effort were resolved, along with the modernization and digitalization of the registration process. Nonetheless, new barriers have emerged such as bottlenecks producing cadastral survey reports, while some entrenched barriers remain unresolved such as fees imposed by non-governmental entities; the Lawyers Syndicate for example. The policy recommendations address both emerging implementation barriers such as devising a cohesive communication strategy employing a pull/push approach, and unresolved ones such as extra-governmental fees by the Lawyers Syndicate.